TINGKAT PENDAPATAN ANGGOTA LMDH “LANCAR JAYA” DARI SEKTOR PERTANIAN HORTIKULTURA DI DESA NGANCAR KECAMATAN NGANCAR KABUPATEN KEDIRI - Erda Risky Saputra; Tatag Muttaqin; Nugroho Tri Waskitho (Journal of Forest Science Avicennia, 2019)
Abstraction       This research was conducted on 10 November 2018 - 31 January 2019 in Ngancar Village, Ngancar District, Kediri Regency. The study was intended to determine the level of income of LMDH "Current Jaya" members in Ngancar Village. In addition, to find out the factors that influence the success of the Forest Village Society Institute (LMDH) program that has been carried out in increasing the income of members of farmer groups. The location of Ngancar Village is due to the fact that the area is one of the tourist areas which has a relatively large number of poor people.       Methods of data collection in the form of primary data collected by direct observation techniques in the field with interviews, questionnaires, and documentation studies of respondents (farmer group members) obtained by purposive sampling method. Secondary data is collected by the technique of recording data that already exists in related institutions. The data obtained will be processed by calculation and tabulation. While in the method of data analysis, researchers used two ways, namely an analysis of economic success (income), and the success factor of LMDH. For data processing methods, the income questionnaire uses the farm income formula (π) which is the difference between total receipt (TR) and total cost (TC), while the questionnaire success factor LMDH uses a Likert Scale.       Based on the results of the research conducted, Chili (Capsicum annum L) commodity was obtained 68 respondents with a total income of Rp. 3,337,850,000, with an average income per hectare of Rp. 49,086,030 in one planting season. While the commodity Tomato (Solanum lycopersicum L) obtained 47 respondents with a total income of Rp. 1,368,899,000, with an average income per hectare of Rp. 29,125,510 in one planting season.Keywords: income, factor, LMDH